Pengaruh Pengangguran Terbuka dan Pertumbuhan Penduduk Terhadap Tingkat Kemiskinan Kabupaten/Kota di Provinsi Lampung Tahun 2020-2022 - Nelmy Fitria Utami; Dea Marsa Amelia; Masna Ani Saputri; Misfi Laili Rohmi (Universitas Kristen Indonesia Toraja, 2025)
This study was conducted to analyze the impact of open unemployment and population on poverty in districts/cities in Lampung Province in 2020-2022. This study uses a quantitative method with a statistical analysis approach to secondary data obtained from the Central Statistics Agency. The data analysis technique uses panel data regression analysis with the help of Eviews software. The results of the analysis show that both partially and simultaneously, the level of open unemployment and population growth do not have a significant effect on poverty in Lampung Province.